2020
DOI: 10.1007/s11255-020-02641-5
|View full text |Cite|
|
Sign up to set email alerts
|

Glomerulosclerosis predicts poor renal outcome in patients with idiopathic membranous nephropathy

Abstract: Objective This study aimed to investigate the association between the proportion of glomerulosclerosis (focal segmental glomerulosclerosis and/or global glomerulosclerosis) and renal prognosis in patients with idiopathic membranous nephropathy (IMN). Methods A retrospective analysis performed from January 2008 to December 2017 in the First Affiliated Hospital of Shenzhen University by renal biopsy confirmed 200 patients with IMN, and their clinical pathology and prognosis were compared. Patients were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…It is characterized by decreased glomerular endothelial cells, the accumulation of mesangial matrix, the proliferation of podocytes, and the thickening of the basement membrane. It is an important pathological basis for ESRD and the outcome event of almost all chronic renal disease progression [ 11 ]. Previous studies have shown that the deposition of subcutaneous immune complexes on the glomerulus may damage the attachment of podocytes and the basement membrane, and the exfoliation of epithelial cells and the basement membrane may lead to GS [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is characterized by decreased glomerular endothelial cells, the accumulation of mesangial matrix, the proliferation of podocytes, and the thickening of the basement membrane. It is an important pathological basis for ESRD and the outcome event of almost all chronic renal disease progression [ 11 ]. Previous studies have shown that the deposition of subcutaneous immune complexes on the glomerulus may damage the attachment of podocytes and the basement membrane, and the exfoliation of epithelial cells and the basement membrane may lead to GS [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, numerous studies have demonstrated that focal segmental glomerulosclerosis (FSGS) disease was a risk factor for poor prognosis in patients with MN [ 9 , 10 ]. Moreover, a Chinese study showed that GS can predict the poor prognosis of primary MN [ 11 ]. However, there have been few cohort studies on patients with MN with NNP.…”
Section: Introductionmentioning
confidence: 99%
“…About 20% of the patients with IMN progress to end-stage renal disease (ESRD) gradually within 5-15 years. 9 M-type phospholipase A2 receptor (m-PLA2R) has been considered to be the major autoantigen of IMN. The Anti-PLA2R antibody has been defined as a suitable biomarker in clinical practice because of its close association with clinical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Persistent elevation of anti-PLA2R antibody levels after effective treatment is a significant predictor of poor prognosis. 8,9 However, whether anti-PLA2R has a relationship with histopathological parameters or BMI has not been proved so far.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation